A Comprehensive Analysis of Cloud Kitchen Operations: Evaluating INDSERV and the Marketing Mix as Factors Influencing Customer Loyalty through Satisfaction - Reinaldilas, Reinaldilas; Ingkadijaya, Rahmat; Trirachmadi Mumin, Adhi (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2023)
Purpose of the study: The aim of this study is to analyze the loyalty of Cloud Kitchen’s user through satisfaction as the impact of industrial service quality and marketing mix. Design/methodology: This study utilizes a quantitative approach with Structural Equation Modelling by using the SmartPLS program and involves responses from respondents selected by purposive sampling method. Findings: The results of this study indicate a direct effect of service quality on satisfaction; marketing mix on satisfaction; and satisfaction on loyalty. Meanwhile, no direct effect of service quality on loyalty; and marketing mix on loyalty was found. However, there is an indirect effect of service quality on loyalty through satisfaction; and marketing mix on loyalty through satisfaction. Research limitations/Implications: This research only measures loyalty based on service quality, marketing mix and customer satisfaction. Further research is needed by looking at other influential aspects and other symptoms or problems that may arise. Novelty/Originality of the study: To analyze the loyalty of Cloud Kitchen’s user as a new culinary business model that utilizes digital technology through satisfaction affected by industrial service quality and marketing mix.